Mapping care trajectories for hospital-initiated benzodiazepine deprescribing in older adults: a multicentre qualitative study - López-Toribio, María; Dalleur, Olivia; Adda, Tokandji Rostand; De Saint-Hubert, Marie; Dikeos, Dimitris; Tsoutsi, Vagioula; Callegari, Enrico; Wyller, Torgeir Bruun; Wichniak, Adam; Kaznowski, Martha; Miralles, Ramón; Pascual, Begoña; et al. (Université d'Ottawa | University of Ottawa, 2025)
Abstract Background Long-term prescription of benzodiazepine receptor agonists (BZRAs) for insomnia in adults over 65 years of age is considered a low-value care practice. Although deprescribing has emerged as a possible solution, the implementation of BZRA deprescribing has been considered insufficient in routine clinical care. Mapping care trajectories relative to BZRA deprescribing can help identify inefficiencies in current care and propose strategies to enhance the implementation of deprescribing interventions in the long term. This study aims to map care trajectories and characterise contextual factors relevant to hospital-initiated BZRA deprescribing in older adults. Methods A qualitative study was conducted with local researchers, healthcare professionals (HCPs), patients, and informal carers in six European countries (Belgium, Greece, Norway, Poland, Spain, and Switzerland). Three theoretical frameworks were used to guide data collection and analyses: 1) the ‘6W’ multidimensional model of care trajectories; 2) the patient-centred deprescribing process; and 3) the Context and Capabilities for Integrating Care framework. Data was collected online through self-administered questionnaires, individual interviews, and group validation interviews. Data were transcribed verbatim and analysed using a combination of deductive and inductive thematic analyses. Results We collected 18 responses to surveys, and conducted 53 interviews (6 local researchers, 36 HCPs, 11 patients or informal carers) and 7 group interviews (comprising 28 HCPs, 4 patients). We developed nine validated care trajectory maps by hospital department and type of unit, and two general comparative maps for inpatient and outpatient care. Hospital-initiated BZRA deprescribing emerged as a complex healthcare process that is likely to involve several HCPs from hospital and primary care. Participants considered patient involvement in shared decision-making (SDM) to be crucial in deprescribing, but implementation was scarce in routine care. The type of HCPs involved and the communication channels between them were specific to each country. Fragmented care and poor communication in the care trajectory hindered follow-up and continuity of care. Conclusions Deprescribing interventions should include context-sensitive strategies to promote patient participation in SDM, foster the use of guidelines, and enhance interprofessional collaboration along the care trajectory. Care trajectory maps can be used as an implementation tool to translate BZRA deprescribing interventions into routine practice.